Posterior Reversible Encephalopathy Syndrome due to Eclampsia in Term Pregnancy - Gurung, T; Shrestha, AB; Shrestha, S (Nepal Journal of Obstetrics and Gynaecology, 2015)
We report a 30 years primigravidae presented in term pregnancy with eclampsia with intrauterine foetal death and underwent instrumental delivery. Peripartum management of eclampsia is always challenging for anaesthesiologist and obstretrician. The case was managed under general anaesthesia and kept on mechanical ventilation for three days. Postpartum cranial computed tomography revealed low attenuated area in right basal ganglia. Low attenuated area in bilateral frontal and parietal lobes with subtle gyral high density in bilateral frontal lobes. Report was suggestive of posterior reversible encephalopathy syndrome. Clinical improvement was observed with supportive treatment and extubated on the third postpartum day. Posterior reversible encephalopathy syndrome is a cliniconeuroradiological syndrome associated with the various conditions including severe hypertension and seizures. Eclampsia is one of the most important causes of posterior reversible encephalopathy syndrome.